Daytime sleepiness in Chinese professional, semi professional and students soccer players in the Shanghai lockdown - You, S.; Cicchella, A. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Purpose April-May 2021 Shanghai city was under strict lockdown. Soccer players suffered from the restrictions, being unable to train and have a social life. The aim of this study was to compare differences in daytime sleepiness between genders and qualification levels in a cohort university Chinese soccer player under 0 Covid policy restrictions in the urban area of Shanghai.